P35 Ability to quantify stereoelectroencephalography (SEEG) electrode trajectory proximity to vessels across imaging protocols. Issue 3 (14th February 2019) - Sparks, R; Vakharia, V; Rodionov, R; Vos, S; McEvoy, A; Miserocchi, A; Duncan, J; Ourselin, S
Abstract : Objectives: Automated planning of stereoelectroencephalography (SEEG) electrode trajectories is dependent on vessel segmentation. 1 We quantify imaging protocols ability to measure trajectory-to-vessel distance. Design: Retrospective analysis. Subjects: Ten consecutive patients were selected whom had SEEG implantation (95 electrodes) and Digital Catheter Subtraction Angiography (DSA) with catheterization of carotid or vertebral arteries, post-gadolinium T1-weighted (GAD), phase-contrast MR angiography and MR venography (MR) acquired. Methods: SEEG trajectories were planned manually with DSA. Minimum distance to vessels and risk 1 were computed for each trajectory using vessel segmentation from GAD, MR, or DSA. Vessel size was considered by including DSA vessels diameters above 1, 2, 3, or 4 mm. Results: Minimum distance to a vessel was 6.2±3.9 mm (GAD), 2.5±1.6 mm (MR), and 1.5±1.2 mm (DSA). Based on DSA vessel size minimum distances were 2.0±1.5 mm (DSA >1 mm), 3.4±2.6 (DSA >2 mm), 6.6±4.6 mm (DSA >3 mm), and 11.8±7.9 mm (DSA >4 mm). Risk was 0.4±0.4 (GAD), 0.8±0.4 (MR), and 1.1±0.2 (all DSA), 1.0±0.2 (DSA >1 mm), 0.7±0.4 (DSA >2 mm), 0.4±0.5 (DSA >3 mm), and 0.2±0.3 (DSA >4 mm). Conclusions: DSA is best able to segment vessels. MR has metrics similar to DSA vessels above 2 mm. GAD has metrics similar to DSA vessels above 3 mm.